2016
DOI: 10.1108/maj-12-2015-1291
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance guidelines compliance and firm financial performance

Abstract: Purpose This paper aims to examine the impact of compliance with corporate governance (CG) guidelines during the period 2002-2014 on firm financial performance and firm value of Kenyan-listed companies. Design/methodology/approach Using panel data of 520-firm year’s observations between 2005 and 2014, the authors test the hypothesis that compliance with CG guidelines issued in 2002 by Capital Markets Authority (CMA) improved firm financial performance and firm value. Findings Compliance with CG Index which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 71 publications
(56 reference statements)
2
38
0
Order By: Relevance
“…The size of the company is measured using the measurement in Haniffa & Cooke (2005), Daniel et al (2010), Haron (2014), Gonçalves & Lopes (2015) and Outa & Waweru (2016) studies; from the book value of company's total assets.…”
Section: Company Sizementioning
confidence: 99%
“…The size of the company is measured using the measurement in Haniffa & Cooke (2005), Daniel et al (2010), Haron (2014), Gonçalves & Lopes (2015) and Outa & Waweru (2016) studies; from the book value of company's total assets.…”
Section: Company Sizementioning
confidence: 99%
“…Adi et al (2013) found financial performance has a positive significant effect on firm value. Outa and Waweru (2016) found financial performance measured by ROA has a positive significant effect on the firm value measured by Tobin's Q. Based on the evidence, the hypothesis in this study is as follows: H3a : Firm performance has a significant positive effect on firm value.…”
Section: Financial Performance and Firm Valuementioning
confidence: 71%
“…The right side is depicted as external governance elements as a result of the firm's need to gain capital. Empirical research proved that internal and external monitoring mechanism of a firm has a direct relationship with the financial power of a firm (Aguilar, 2016;Outa & Waweru, 2016). Monitoring refers to the effort of the firm's owner to mitigate the manager's opportunistic behavior (Mohamad Nur .…”
Section: Monitoring Mechanismmentioning
confidence: 99%